THE ESSENCE OF INTERNATIONAL LABOR MIGRATION AND ASSESSMENT OF THE CURRENT LEVEL OF UKRAINE'S INTEGRATION INTO THE INTERSTATE LABOR MARKET - Zelinska , O.M. (The actual problems of regional economy development, 2020)
Labor migration affects public life, and plays an important role in the development of socio-economic relations, which, in turn, affects political development. Therefore, the relevance of this article lies in the global nature and rapid growth of domestic and interstate movements of the population and labor resources in various forms, due primarily to the uneven socio-economic development of countries. The volume of international migration is growing every year. More and more labor resources are involved in it. This fact confirms the importance of studying international labor migration as one of the main forms of world economic relations, and its impact on the world economy. The importance of studying the processes of labor migration is due to the rapid growth of their volumes, increasing intensity, a significant impact on the social and economic development of the state. Features of migration processes at this stage of society are their dynamism, rapid response to changes in society and the economy. In this article, the object of study is the interstate exchange of labor. The subject of the study is the theoretical aspects of international labor migration in Ukraine, as well as current trends in labor movement. The main research methods used in the study were general philosophical, dialectical, logical-semantic, synthesis method, system-structural, sociological, and statistical method. The most important is the general philosophical method, because the study of migration processes has its roots in depth, which should be explored with the help of philosophical justification. The use of the dialectical method of cognition is due to the ability to explore migration issues in the unity of economic, social, moral and legal content. The method of synthesis provides an opportunity to add new definitions to the categorical apparatus.